2016
DOI: 10.1007/s10867-016-9415-6
|View full text |Cite
|
Sign up to set email alerts
|

Probing the binding mechanisms of α-tocopherol to trypsin and pepsin using isothermal titration calorimetry, spectroscopic, and molecular modeling methods

Abstract: α-Tocopherol is a required nutrient for a variety of biological functions. In this study, the binding of α-tocopherol to trypsin and pepsin was investigated using isothermal titration calorimetry (ITC), steady-state and time-resolved fluorescence measurements, circular dichroism (CD) spectroscopy, and molecular modeling methods. Thermodynamic investigations reveal that α-tocopherol binds to trypsin/pepsin is synergistically driven by enthalpy and entropy. The fluorescence experimental results indicate that α-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…At the same time, it was shown that lipids can bind to digestive enzymes and inhibit their activity. For example, α-tocopherol in the steady-state fluorescence experiments bound to pepsin and inhibited its ability to cleave casein [34]. Here, we analyzed the pepsin spatial structure and revealed the presence of hydrophobic areas on its surface, one of which is located in the region of the catalytic site of the enzyme (Figure 6A).…”
Section: Discussionmentioning
confidence: 96%
“…At the same time, it was shown that lipids can bind to digestive enzymes and inhibit their activity. For example, α-tocopherol in the steady-state fluorescence experiments bound to pepsin and inhibited its ability to cleave casein [34]. Here, we analyzed the pepsin spatial structure and revealed the presence of hydrophobic areas on its surface, one of which is located in the region of the catalytic site of the enzyme (Figure 6A).…”
Section: Discussionmentioning
confidence: 96%
“…(2). According to the Li & Ni (2016) and Li & Yan (2017), a linear Stern-Volmer plot meant that only one type of quenching mechanism occurred (dynamic or static). In the present case, a linear Stern-Volmer plot was observed for GSP ( Fig.…”
Section: Fluorescence Emission Spectroscopymentioning
confidence: 99%
“…For trypsin, there are 2 fundamental characteristics of the active site region. The first one is formed by the 3 catalytic residues His 57, Asp 102, and Ser 195; the second one is that there is a ‘pocket’ near Ser‐195 defining the cut position of the peptidic bond . As from Figure d2, the binding site is in a “pocket” near Ser‐195.…”
Section: Resultsmentioning
confidence: 99%